2023
DOI: 10.3390/life13122247
|View full text |Cite
|
Sign up to set email alerts
|

Stem-Cell-Derived Extracellular Vesicles: Unlocking New Possibilities for Treating Diminished Ovarian Reserve and Premature Ovarian Insufficiency

Yana O. Martirosyan,
Denis N. Silachev,
Tatiana A. Nazarenko
et al.

Abstract: Despite advancements in assisted reproductive technology (ART), achieving successful pregnancy rates remains challenging. Diminished ovarian reserve and premature ovarian insufficiency hinder IVF success—about 20% of in vitro fertilization (IVF) patients face a poor prognosis due to a low response, leading to higher cancellations and reduced birth rates. In an attempt to address the issue of premature ovarian insufficiency (POI), we conducted systematic PubMed and Web of Science research, using keywords “stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 191 publications
0
3
0
Order By: Relevance
“…In addition, O 3 exposure is inversely related to the ovarian reserve. It is found that exposure to O 3 is positively associated with low excretion of anti-Muellerian hormone (AMH), an important marker for ovarian reserve ( 32 ). However, some studies showed that exposure to O 3 was effective in treating female infertility.…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%
“…In addition, O 3 exposure is inversely related to the ovarian reserve. It is found that exposure to O 3 is positively associated with low excretion of anti-Muellerian hormone (AMH), an important marker for ovarian reserve ( 32 ). However, some studies showed that exposure to O 3 was effective in treating female infertility.…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%
“…Owing to the deleterious impact of environmental pollution, psychological stress, and unhealthy lifestyles, infertility has witnessed a marked uptick in recent years and emerged as a pressing global health issue [ 1 , 2 , 3 , 4 ]. In a recent report published by the World Health Organization in 2022, it was estimated that the global prevalence of infertility stands at 17.5%, with the Western Pacific region exhibiting the highest rates, peaking at 23.2% [ 5 , 6 ]. Over the past two decades, China has witnessed a rise in infertility rates among those of reproductive age from 2.5–3.0% to 12.5–18.0% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, data from clinical trials are still inconclusive as to HUMSCs' safety for the restoration of reproductive aging [34]. Amniotic fluid stem cells have shown an ability to differentiate into granulosa cells, which can counter or prevent follicular atresia and keep follicles healthy [35]. Still, more conclusive data are needed for human applications, since currently available results of MSC research in female-infertility-related diseases are mostly limited to findings in animal models and the underlying dynamics involving MSCs and several conditions causing female infertility have not yet been clarified [36].…”
mentioning
confidence: 99%